Leadership of the Regional Director of Kolaka Enterprises Company (PERUSDA Kolaka) - askari zakariah (IAI Al-Mawaddah Warrahmah Kolaka, 2022)
One of the problems of BUMD is related to the roles and responsibilities of the board of directors and supervisory board in the management of BUMD. Perusda kolaka businesses need to think about market development, product development, innovation, horizontal integration, vertical integration, concentric diversification, and conglomeration diversification. Based on news perusda was faced to many problem such as Allegedly Activities in HPK Area Without IPPKH, and Income to Local Government (PAD ke Pemerintah Kabupaten) revenue in 2019 was Rp. 350,000,000 is low income category. Furthermore, perusda need strategic leadership. Government of Republic Indonesia has released rules for election director of perusda Peraturan Pemerintah Nomor 54 Tahun 2017 tentang Badan Usaha Milik Daerah and Peraturan Menteri Dalam Negeri Nomor 37 Tahun 2018 tentang Pengangkatan dan Pemberhentian Anggota Dewan Pengawas atau Anggota Komisaris dan Direksi pada Badan Usaha Milik Daerah.